Estradiol modulates the anorexic response to central glucagon-like peptide 1 - Maske, Calyn B. (Horm Behav, 2017)
Estrogens suppress feeding in part by enhancing the response to satiation signals. Glucagon-like peptide 1 (GLP-1) acts on receptor populations both peripherally and centrally to affect food intake. We hypothesized that modulation of the central GLP-1 system is one of the mechanisms underlying the effects of estrogens on feeding. We assessed the anorexic effect of 0, 1, and 10 μg doses of GLP-1 administered into the lateral ventricle of bilaterally ovariectomized (OVX) female rats on a cyclic regimen of either 2 μg β-estradiol-3-benzoate (EB) or oil vehicle 30 min prior to dark onset on the day following hormone treatment. Central GLP-1 treatment significantly suppressed food intake in EB-treated rats at both doses compared to vehicle, whereas only the 10 μg GLP-1 dose was effective in oil-treated rats. To follow up, we examined whether physiologic-dose cyclic estradiol treatment influences GLP-1-induced c-Fos in feeding-relevant brain areas of OVX females. GLP-1 significantly increased c-Fos expression in the area postrema (AP) and nucleus of the solitary tract (NTS), and the presence of estrogens may be required for this effect in the paraventricular nucleus of the hypothalamus (PVN). Together, these data suggest that modulation of the central GLP-1 system may be one of the mechanisms by which estrogens suppress food intake, and highlight the PVN as a region of interest for future investigation.